2021
DOI: 10.1097/qai.0000000000002614
|View full text |Cite
|
Sign up to set email alerts
|

Constructions of HIV Risk Among a Diverse Sample of HIV-Negative Young Men Who Have Sex With Men Who Are Repeat Testers

Abstract: Introduction. To end the HIV epidemic, HIV prevention and pre-exposure prophylaxis (PrEP) promotion efforts must reach young men who have sex with men (YMSM) at greatest risk for HIV. This study qualitatively explored whether an objective used to objectively assess HIV risk aligned with how YMSM conceptualize their risk for HIV, and the factors that shape YMSM's risk perceptions.Methods. Interviews with a racially/ethnically diverse sample of HIV-negative YMSM (ages 19-24, 60% Latinx; n=20) examined conceptual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…This study found that almost a quarter of the patients diagnosed with syphilis through routine ED screening started PrEP, whereas none of those without syphilis did, despite more than half of this latter group's survey answers indicating that they should be recommended PrEP 5 . Previous studies have suggested that low perceived risk is a major barrier to PrEP uptake, even in individuals reporting behaviors that increase HIV risk 2–4 . Although it is difficult to know if the participants in the present study already perceived their HIV risk to be high before their syphilis diagnosis, at the time of participation in the study, a much higher proportion of patients with syphilis perceived their HIV risk to be moderate to large compared with syphilis-negative patients with PrEP indications (16.2% vs. 7.1%).…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…This study found that almost a quarter of the patients diagnosed with syphilis through routine ED screening started PrEP, whereas none of those without syphilis did, despite more than half of this latter group's survey answers indicating that they should be recommended PrEP 5 . Previous studies have suggested that low perceived risk is a major barrier to PrEP uptake, even in individuals reporting behaviors that increase HIV risk 2–4 . Although it is difficult to know if the participants in the present study already perceived their HIV risk to be high before their syphilis diagnosis, at the time of participation in the study, a much higher proportion of patients with syphilis perceived their HIV risk to be moderate to large compared with syphilis-negative patients with PrEP indications (16.2% vs. 7.1%).…”
Section: Discussionmentioning
confidence: 57%
“…5 Previous studies have suggested that low perceived risk is a major barrier to PrEP uptake, even in individuals reporting behaviors that increase HIV risk. [2][3][4] Although it is difficult to know if the participants in the present study already perceived their HIV risk to be high before their syphilis diagnosis, at the time of participation in the study, a much higher proportion of patients with syphilis perceived their HIV risk to be moderate to large compared with syphilis-negative patients with PrEP indications (16.2% vs. 7.1%). Furthermore, participants with syphilis were more than 3 times as likely to state that they might, probably, or definitely would start PrEP in the next 6 months (49.0% vs. 14.9%).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Unprotected exposure to multiple partners during group sex is a plausible scenario, especially when also involving chemsex [ 22 ]. Moreover, younger MSM have been identified as a potentially vulnerable group for HIV-infection due to their relatively large sexual networks and relative unawareness of sexual behaviours associated with increased STI/HIV risk [ 23 ]. It could be helpful to additionally apply these determinants as co-indicators for PrEP eligibility.…”
Section: Discussionmentioning
confidence: 99%